2014
DOI: 10.1089/lap.2014.0056
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Efficacy and Safety Between a Segmental Thermo-expandable Metal Alloy Spiral Stent (Memokath 051) and a Self-Expandable Covered Metallic Stent (UVENTA) in the Management of Ureteral Obstructions

Abstract: The UVENTA achieved a higher clinical success rate than the Memokath 051. Our study demonstrated that the UVENTA is safe and effective in the management of benign and malignant ureteral obstruction. The complications were similar between the two metallic stents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…The studies were published over a period of 23 years (1992–2016) and included 21 prospective and 10 retrospective studies. These studies reported the effectiveness of specific MSs in population studies [1] , [2] , [3] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , in comparative studies between different MSs [28] and between MSs and JJ stents [29] , [30] . It should be noted that all comparative studies were retrospective in nature.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies were published over a period of 23 years (1992–2016) and included 21 prospective and 10 retrospective studies. These studies reported the effectiveness of specific MSs in population studies [1] , [2] , [3] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , in comparative studies between different MSs [28] and between MSs and JJ stents [29] , [30] . It should be noted that all comparative studies were retrospective in nature.…”
Section: Resultsmentioning
confidence: 99%
“…The Memokath 051 was reported to have patency rates ranging between 82% and 100%. The most common complication was stent migration, with an incidence ranging between 10.8% and 17.4% of the stented ureters [2] , [5] , [14] , [22] , [26] , [28] , [30] . The Memokath 051 is a stent that has been used and studied for many years, especially from 1999 to 2014 ( Table 2 , Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 Although more studies are required, several recent articles about UVENTA stent efficacy The efficacy of UVENTA ureteral stenting has been compared with those of PDJ and Memokath 051. 26,27 Most metal stent placements are performed to achieve long-lasting patency and to decrease complications in patients with extrinsic MUO. However, several patients have undergone additional procedures after the placement of ureteral metal stents due to decreased function.…”
Section: Commentsmentioning
confidence: 99%